A Horizont 2020 program és az inkluzív, innovatív és reflektív társadalmak létrehozásának kihívásai - Szilágyi, Dániel (Közép-Európai Közlemények, 2017)
The primary reason behind the choice of topic for the presented research was the fact that the rapid development of information society in the recent years has brought forth a significant increase in the importance of innovation and research and development systems globally. This process has also affected the priorities of the European Union, leading to the adoption of the new objectives of establishing a European Research Area and creating an „innovative union” – for the furthering of these objectives, the Council and the Parliament adopted a regulation in 2013 about the establishment of the “Horizon 2020” framework programme for research and innovation. This study seeks to present a general overview of the concept of the innovative union and a more thorough analysis of the instruments of the Horizon 2020 programme that serve the furtherance of social inclusion, paying particular attention to the “pillar” of tackling societal challenges. A main objective of the research is the examination of whether the biennial work programmes designed for the implementation of the framework are effective in the achievements of the objectives set forth in the field of social inclusion; furthermore, what new solutions the current (2016–2017) work programme proposed to remedy the deficiencies that arose during the runtime of the previous work programme. The fact that the execution of the framework programme is currently underway serves to prove that the choice of topic is relevant to current issues; while the near complete lack of Hungarian – and to a lesser extent, foreign-language – literature in the examined area supports the necessity of research.